2011
DOI: 10.1007/s00406-011-0263-x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to changes during antidepressant treatment: a comparison of unidimensional subscales of the Inventory of Depressive Symptomatology (IDS-C) and the Hamilton Depression Rating Scale (HAMD) in patients with mild major, minor or subsyndromal depression

Abstract: In the efficacy evaluation of antidepressant treatments, the total score of the Hamilton Depression Rating Scale (HAMD) is still regarded as the 'gold standard'. We previously had shown that the Inventory of Depressive Symptomatology (IDS) was more sensitive to detect depressive symptom changes than the HAMD17 (Helmreich et al. 2011). Furthermore, studies suggest that the unidimensional subscales of the HAMD, which capture the core depressive symptoms, outperform the full HAMD regarding the detection of antide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 58 publications
(99 reference statements)
0
23
0
1
Order By: Relevance
“…For sertraline 200 mg, the effect size was 0.38 on HAM-D 6 and 0.20 on HAM-D 17 . In the placebo-controlled sertraline study by Helmreich et al [37], only the effect size for HAM-D 6 was shown, namely 0.46. In the study by Martiny et al [38], focusing on adjunctive bright light to sertraline in non-seasonal major depression, the effect size was 0.66 on HAM-D 6 and 0.45 on HAM-D 17 .…”
Section: Resultsmentioning
confidence: 99%
“…For sertraline 200 mg, the effect size was 0.38 on HAM-D 6 and 0.20 on HAM-D 17 . In the placebo-controlled sertraline study by Helmreich et al [37], only the effect size for HAM-D 6 was shown, namely 0.46. In the study by Martiny et al [38], focusing on adjunctive bright light to sertraline in non-seasonal major depression, the effect size was 0.66 on HAM-D 6 and 0.45 on HAM-D 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Depressive symptoms have been shown consistently to be associated with cognitive impairments,53 and these symptoms could impair learning and the application of new adaptive behaviors. However, the severity level of depression in both samples was relatively low and did not reach diagnostic thresholds for a current depressive episode in most individuals 54. This might explain why potential cognitive effects of depression did not affect treatment outcome in this study.…”
Section: Discussionmentioning
confidence: 66%
“…This scale has been widely used in clinical trials and serves as gold standard for assessment of depression. It has been found valid and reliable measurement outcome with a higher inter-rater reliability and test-retest reliability [59, 61]. …”
Section: Methodsmentioning
confidence: 99%